GAMMA-RAY TRANSITIONS FROM LOWEST T=2 STATES OF NA-24 AND AL-28 - Start, D; Jelley, N; Burde, J; Hutcheon, D; Randolph, W; Underwoo, B; Warner, R (1973)
The γ-ray decay modes of the lowest 0+, f = 2 states of 24Na and 28Al have been investigated with a Ge(Li) detector in the 22Ne(3He, p)24Na and 26Mg(3He, p)28Al reactions. Precise excitation energies of 5970.2 ± 0.9 keV and 5992.4 ± 0.4 keV were obtained for the 24Na and 28Al T = 2 states respectively. These energies are used to calculate the masses of the Tz = -1 and -2 members of each isobaric quintet and the branching ratios are compared with those of the analogous isovector M1 transitions in 24Mg and 28Si and also with shell model calculations. © 1973.